Unintentional dexamethasone and steroid abuse among Yemeni patients: a case series - Butheinah A. Al-Sharafi (Journal of Clinical and Translational Endocrinology Case Reports)
Background: Glucocorticoids are widely used for various medical conditions, but their unregulated availability in Yemen has led to inadvertent long-term steroid use, resulting in exogenous Cushing syndrome and secondary adrenal insufficiency. This case series highlights instances of unintentional dexamethasone abuse among Yemeni patients. Cases: We describe five patients who developed glucocorticoid dependence after using dexamethasone in various formulations, including injections, syrup, topical creams, and herbal remedies. These patients exhibited symptoms of Cushing's syndrome, and in some cases, hypoadrenalism upon discontinuation. Discussion: The patients were unaware of the risks associated with long-term steroid use. Some continued use due to withdrawal symptoms, while others were unknowingly exposed through herbal remedies. Treatment involved corticosteroid tapering, but in some cases, prolonged dependence on low-dose steroids persisted. Conclusion: The unrestricted availability of dexamethasone and other steroid preparations in Yemen has led to widespread unintentional steroid abuse, resulting in severe complications and irreversible hypoadrenalism in many patients. Raising awareness among healthcare providers and the general public is essential to mitigate this issue and ensure appropriate use of glucocorticoids.